Comparative Aspects of the Common Law and Civil Law Legal Families (Journal of actual problems of jurisprudence, 2021)
The research topic is devoted to a comparative analysis of the Anglo-American and Romano-Germanic legal families. The purpose of scientific research is to identify the most important distinctive features of these legal families and the possibility of their convergence. It is assumed that the convergence processes between the Anglo-American and Romano-Germanic legal families will deepen and the issues of implementing new legal institutions in national law will become important in the future.For these purposes, the author examined the main classifications of legal families, analyzed the application of the terms «English law», «general law», «Anglo-Saxon law» in the legal literature.At present, the issue of the implementation of English law in the national legislation of Kazakhstan has been actively discussed with the establishment of the International Financial Center «Astana». Implementation of foreign legal institutions and concepts should be carried out after a comprehensive and in-depth complex study of all negative and positive factors, including taking into account socio-economic, historical and cultural differences in society. In this regard, the study has theoretical value, since it allows us to identify possible problems of application and perception of English law rules in national law.Key words: legal family, Anglo-American law, English law, common law, Romano-Germanic law, family of continental law.